Streptomyces strain P42 as a potent biological control against chilli anthracnose disease caused by Colletotrichum spp. - Shahbazi, P.; Musa, M.Y.; Tan, G.Y.A.; Avin, F.A.; Teo, W.F.A.; Vikineswary, S. (Gaurav Society of ARIC, Hisar, India, 2013)
A total of 130 actinomycetes was isolated from rhizospheres of healthy and diseased (Colletotrichum-infected) chilli plants and tested for their inhibitory activity against Colletotrichum acutatum, Colletotrichum gloeosporioides and Colletotrichum truncatum. Twenty-six isolates were active against at least one of the Colletotrichum species and 12 were active against all three anthracnose fungi. Four bioactive isolates, P8, P39, P42 and P115, that exerted high inhibitory activity against all three anthracnose fungi species, were identified using molecular methods. Phylogenetic analysis of the 16S rRNA gene sequences revealed that all four isolates belonged to the genus Streptomyces. Strain P42, which showed the highest inhibitory activity, was further tested as biological control agent in a greenhouse study. This strain successfully controlled chilli anthracnose disease by significantly reducing the disease severity. The results of the current study not only revealed that rhizosphere of Colletotrichum-infected chilli plants contained more bioactive streptomycete which are bioactive against Colletotrichum spp. than rhizosphere of healthy chilli plants, but also demonstrated the efficacy of biological control through soil suppression.